2009
DOI: 10.1007/s11270-009-0078-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Poultry Litter Application Methods on the Longevity of Nutrient and E. coli in Runoff from Tall Fescue Pasture

Abstract: Significant quantities of the broiler chicken (Gallus gallus domesticus) litter produced in the USA are being applied to pasture lands. The traditional surface-broadcast application of animal manure onto permanent pasture, however, may lead to high concentration of nutrients and pathogenic microorganisms near the soil surface that could be transported off site by runoff water. Subsurface banding of poultry litter has the potential to reduce nutrient and pathogen losses through runoff. However, this has not bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 28 publications
0
34
1
Order By: Relevance
“…Clear understanding of the transport of pathogens potentially present in poultry wastes and its runoff is essential for the establishment of effective control strategies to reduce the adverse impact on environment, food safety, and public health. Sistani et al [60] compared two methods of poultry litter application, surface broadcast and subsurface banding, to investigate the influence of application methods on E. coli concentration in runoff from tall fescue pasture. E. coli concentration was found to be significantly higher in runoff from broadcast application than subsurface banding treatment.…”
Section: Food Safety and Human And Animal Health Issues Associated Wmentioning
confidence: 99%
“…Clear understanding of the transport of pathogens potentially present in poultry wastes and its runoff is essential for the establishment of effective control strategies to reduce the adverse impact on environment, food safety, and public health. Sistani et al [60] compared two methods of poultry litter application, surface broadcast and subsurface banding, to investigate the influence of application methods on E. coli concentration in runoff from tall fescue pasture. E. coli concentration was found to be significantly higher in runoff from broadcast application than subsurface banding treatment.…”
Section: Food Safety and Human And Animal Health Issues Associated Wmentioning
confidence: 99%
“…Poultry manure (PM) is an excellent source of phosphorous, nitrogen, potassium, and other nutrients essential for plant growth, and is therefore is applied to cropland in the United States (US), Canada, the European Union, and China, in lieu of, or in addition to, commercial fertilizer (Oenema et al, 2007;Sistani et al, 2010). In the US state of Iowa, alone, over 15 billion eggs are produced annually (UDSA-NASS, 2014), resulting in the generation of over 5.6 million Mg of fresh layer manure (Naber and Bermudez, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…These systems move water quickly to surface waters, decreasing the soil's natural capacity for filtration. Bacterial transport in runoff from application of various types of manures, including poultry, has been widely studied (Soupir et al, 2006;Jenkins et al, 2008;Brooks et al, 2009;Harmel, 2009;Guzman et al, 2010;Sistani et al, 2010;Delgado et al, 2011). Laboratoryscale studies have shown that SALM and other pathogens can be transported through over 1 m of soil, and transport is controlled by soil types, hydrodynamic forces, physical filtration, and interactions between bacterial surface-charges and air, water, and soil interfaces (Haznedaroglu et al, 2009;Bech et al, 2010;Chen, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Levels of thermotolerant coliforms, E. coli , and enterococci in the present study were also relatively low and not different between L+ and L– soils (Table 3). Background or natural levels of E. coli and other fecal indicators have frequently been measured for runoff studies in control soils not receiving litter and in soils before litter application (Jenkins et al, 2006; Brooks et al, 2009; Sistani et al, 2010). Contributions of indicator and pathogenic bacteria by livestock, pets, wild animals, and birds is well established (Reed et al, 2003; USGS, 2009), and estimates of their background levels are factored into watershed runoff models (Liu et al, 2010).…”
Section: Resultsmentioning
confidence: 99%